Analysis of agreement of assessment tools of range of motion in the elderly - Pires-Oliveira, Deise Aparecida de Almeida; Freitas, Rosemari Queiroz; Júnior, Abdallah Achour; Oliveira, Laís Campos de; Oliveira, Raphael Gonçalves de; Oliveira-Silva, Iranse; Soares, Viviane; Oliveira, Rodrigo Franco de (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Considering the growth of the elderly population and the typical declines in the aging process on physical capacities such as flexibility, it is necessary to understand how different assessment instruments are able to measure joint range of motion. Objective: To verify the agreement between the goniometer and fleximeter instruments in the evaluation of the range of motion of the hip, knee and ankle joints of elderly women. Methods: The study evaluated a total of 138 elderly women, mean age of 70 years (± 5.49). The goniometer and the fleximeter were used to verify the range of motion of the hip flexion, knee flexion and ankle dorsi- and plantar‐flexion. For the analysis were used the Intraclass Correlation Coefficient (ICC) and Bland-Altman plot, with confidence intervals of 95%. Results: The ICC values showed excellent agreement between the instruments, while the Bland-Altman plots presented a low risk of bias for all the regions evaluated (hip flexion: ICC= 0.99, bias= 1.19; knee flexion: ICC= 0.99, bias= -0.16; ankle dorsiflexion: ICC= 0.91, bias= -0.60; ankle plantar-flexion: ICC= 0.96; bias= -0.81). Conclusion: The results showed an excellent agreement between the data provided by the goniometer and fleximeter instruments on the evaluation of the range of motion of the hip flexion, knee flexion and ankle dorsi- and plantar-flexion, indicating that both provide similar results in the elderly.